2015
DOI: 10.3917/rdli.084.0091
|View full text |Cite
|
Sign up to set email alerts
|

Dialoguer plus, mais sur quoi ? Les régulations d’entreprise en matière d’emploi, de formation et de conditions de travail en temps de crise

Abstract: La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accord préalable et écrit de l'éditeur, en dehors des cas prévus par la législation en vigueur en France. Il est précisé que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
(9 reference statements)
2
10
0
4
Order By: Relevance
“…Our first finding is that the implementation of internal or external flexibility adjustments by establishments goes hand-in-hand with active industrial relations, namely, trade union presence, bargaining and disputes. This finding is consistent with the intensified bargaining that was seen during the crisis in France (Béthoux et al, 2015), Germany (Bellmann and Gerner, 2012;Zagelmeyer, 2016;Zagelmeyer, Heckmann and Kettner, 2012), and in Europe as a whole (Glassner, Keune and Marginson, 2011). We can interpret this finding either as an indication that industrial relations did not prevent adjustments, or that the actions of trade unions contained the scale of adjustments.…”
Section: Discussion Of Empirical Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Our first finding is that the implementation of internal or external flexibility adjustments by establishments goes hand-in-hand with active industrial relations, namely, trade union presence, bargaining and disputes. This finding is consistent with the intensified bargaining that was seen during the crisis in France (Béthoux et al, 2015), Germany (Bellmann and Gerner, 2012;Zagelmeyer, 2016;Zagelmeyer, Heckmann and Kettner, 2012), and in Europe as a whole (Glassner, Keune and Marginson, 2011). We can interpret this finding either as an indication that industrial relations did not prevent adjustments, or that the actions of trade unions contained the scale of adjustments.…”
Section: Discussion Of Empirical Resultssupporting
confidence: 82%
“…During the crisis, an increased reliance on this type of bargaining helped drive the decentralization of industrial relations (Glassner, Keune and Marginson, 2011;Béthoux et al, 2015).…”
Section: What Role Did Industrial Relations Play In Responses To the mentioning
confidence: 99%
“…In addition, as documented by Palpacuer and Signeur (2019), the workplace struggle at FT set in motion a series of state interventions that strengthened unions' institutional power resources. Social dialogue on psychosocial risks has since become increasingly common in French firms, though its impact on management strategy is uneven (Béthoux et al 2015). The 2019 court ruling holding management and the company responsible for 'moral harassment' sets a legal precedent that will likely make it easier for unions to challenge management practices in the courts on the basis of their impact on worker health.…”
Section: Discussionmentioning
confidence: 99%
“…Case studies in France have shown evidence of union success in mobilizing power resources to gain favorable results in cases of major organizational restructuring and downsizing (Dupuis, 2018); most visibly in the case of tactics relying on 'Bossnapping' to achieve short-term gains (Parsons, 2013). Survey and case study findings suggest that French unions may be changing their 'repertoire of collective action' toward intensified participation, via 'strategic workforce management' and 'method agreements' (Didry 2013: p.533), with particular emphasis on psychosocial issues (Béthoux et al 2015). At the same time, Béthoux and Mias (2019) find that these social dialogue practices and outcomes vary significantly at the local level, due to differences in how local management and unions react to similar legal requirements.…”
Section: Methods and Case Selectionmentioning
confidence: 99%
“…En estas negociaciones, los trabajadores hacen ciertas concesiones al empleador (a menudo en relación con su salario) a cambio de que este se comprometa a mantener determinadas condiciones (generalmente relativas al empleo). Durante el periodo de crisis, la proliferación de este tipo de negociaciones ayudó a impulsar el fenómeno de la descentralización de las relaciones laborales (Glassner, Keune y Marginson, 2011;Béthoux et al, 2015).…”
Section: El Papel De Las Relaciones Laborales En Respuesta a La Gran unclassified